The unheard stories of the Rohingyas : ethnicity, diversity and media - Ullah, A. K. M. Ahsan; Chattoraj, Diotima (Bristol University Press, 2023)
The 2017 persecution of the Rohingyas resulted in around a million Rohingyas fleeing to Bangladesh, India and Malaysia. This book investigates the complex challenges of managing the large-scale refugee exodus in Bangladesh and how best to resolve these challenges in the future. Using a mixed method approach that includes a survey, key informant interviews and numerous short case studies of persecution, the authors also examine the problematic influence of the media, as local depictions of Rohingya refugees often caused further tension and divides in the midst of the refugee crisis. The book's analysis offers a deeper understanding of the causes and drivers of identity-based politics among Myanmar's Rohingya.